1982
DOI: 10.1002/j.1537-2197.1982.tb13294.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variation in Floral Morphology on Pollination Mechanisms in Asclepias Tuberosa L., Butterflyweed (Asclepiadaceae)

Abstract: Field observations revealed the presence of fruit‐producing (fruiting) and non‐fruit‐producing (non‐fruiting) plants in two south central Oklahoma populations of Asclepias tuberosa L. Comparative measurements of floral characteristics between fruiting and non‐fruiting plants indicated that fruiting plants have significantly larger alar fissure widths and a greater percentage of intact pollinaria. The smaller alar fissure width on flowers of non‐fruiting plants apparently reduces the probability of successful p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…These investigations have often shown that variation in the size of flowers or floral parts translates into differences in seed production and outcrossing rate (erg. Beare & Perkins, 1982;Harder et al, 1985;Thomson & Stratton, 1985;Nilsson, 1988).…”
Section: Introductionmentioning
confidence: 92%
“…These investigations have often shown that variation in the size of flowers or floral parts translates into differences in seed production and outcrossing rate (erg. Beare & Perkins, 1982;Harder et al, 1985;Thomson & Stratton, 1985;Nilsson, 1988).…”
Section: Introductionmentioning
confidence: 92%
“…A CENTRAL POSTULATE of the theory of plant/ pollinator coevolution is that the size, arrangement, and shape of flower parts have evolved to improve the efficiency of pollination or the number ofpollen grains delivered to the stigma surface during a pollinator visit. This view has been elaborated by Stebbins (1971) and supported by many empirical studies (e.g., Beattie, 1971;Beare and Perkins, 1982;Waser and Price, 1984;Thomson and Stratton, 1985;Galen and Newport, 1987;Campbell, 1989). In contrast to effects on female reproduction, the relationship of flower form to male components of reproductive success has received less attention (but see Campbell, 1989).…”
mentioning
confidence: 97%
“…Its unusual pollination system, found in the Asclepiadaceae and Orchidaceae, allows pollen removal, receipt and presence on pollinators to be readily quantified (e.g. Macior, 1965;Kephart & Heiser, 1980;Beare & Perkins, 1982;Morse, 1982;Wolfe, 1987). In the Asclepiadaceae, numerous pollen grains are clustered 102 J.S.SHORE in pollinia which are commonly dispersed in pairs (as pollinaria).…”
Section: Introductionmentioning
confidence: 99%